General purpose physiostimulator. - Porter Gutierrez, F. R.; Llerena Fernández, J. E.; Yonemoto Medina, R.; Reyes Esparza, J. A. (Revista Mexicana de Ingenieria Biomedica, 1991)
The design of a general-purpose physostimulator is described, which can provide voltages from + - 10 mV to + - 10V at frequencies from 0.01 to 1000 Hz, variable duty cycle, train timing, and delay from 0.1 to 1000 ms between pairs of pulses, to be used in the practices of the Department of Biophysics and Physiology of the Unit.